BIOMASSA SEBAGAI MATERIAL ELEKTRODA SUPERKAPASITOR - Nur Adi Saputra; Wasrin Syafii; Gustan Pari; Deded Sarip Nawawi; Akhiruddin Maddu (Jurnal Penelitian Hasil Hutan, 2022)
Electrical storage and distribution devices become important in next generation to help integrate more renewable energy intothe electricity grid. Supercapacitor technology is considered the most promising alternative to Li-ion batteries, which have limitedLithium material. However, the low energy density is a weakness of supercapacitors, even though they have a high-power density.Activated carbon-based supercapacitor electrodes have ideal potential for development. The inherent attributes of activated carbon,pore properties, and functional groups, are responsible for improving the performance of supercapacitors. The main challenge for theresearchers is the pore size distribution, micro (<2nm), meso (2–50 nm), and macro (>50 nm), which varied in activated carbon.Micro pores have an impact on increasing the value of specific capacitance values which will encourage an increase in energy density.Meso pores have an impact on the overall accessibility of the electrode surface by electrolyte ions. Future studies will emphasize oncarbonization and activated carbon activation techniques to improve the surface quality of activated carbon.